Modelling the joint association of socio-economic disadvantage, diabetes, and obesity on COVID-19 mortality in Greater Mexico City - Alejandro Lome-Hurtado; Manuel Soto-Pérez (Scientific Reports)
Abstract The impact of Coronavirus disease 2019 (COVID-19) has severely affected populations with lower socioeconomic background and with certain comorbidities. Many studies have examined the effect of poor socioeconomic conditions or specific comorbidities separately on COVID-19 mortality. However, it is important to understand the joint effect of deprived socioeconomic conditions and specific comorbidities on COVID-19 mortality. Such a joint effect may play a different role in dying of COVID-19, when compared with the effect of deprived socioeconomic conditions and comorbidities separately. Therefore, this study investigates the joint association of deprived socioeconomic background and severe comorbidities (diabetes and obesity) on COVID-19 mortality, in Greater Mexico City. The study used official Mexican COVID-19 data at the individual and municipal level. The results illustrate significant and positive association of the socioeconomic deprivation index along with diabetes and obesity on COVID-19 mortality. This underscores the need for individualized, targeted, and public interventions that consider the role of lower socioeconomic status and specific comorbidities to reduce mortality.